2019
DOI: 10.1007/s42452-019-0397-4
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbons (PAHs) contamination of soils and water around automobile repair workshops in Eket metropolis, Akwa Ibom State, Nigeria

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are very toxic and persistent environmental contaminants. The paper is aimed at investigating the PAHs levels in soil collected at 0-30 cm depths from 5 automobile repair workshops within Eket metropolis/the underground water around its vicinity. The soils and water were prepared in the laboratory following standard procedures and were analysed for 16 US EPA priority PAHs using Gas Chromatography-Mass Spectrometer (GC-MS). Total PAHs concentrations in soil (Ʃ16 EPA PAHs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Reports have shown that indiscriminate spilling of petroleum products around automechanic workshops due to automobile repairs contributes to increased PAH levels in such environment (Farombi et al 2013;Obini et al 2013;Nwoko et al 2017). The mean PAH concentrations of the present study compared to related studies in Nigeria revealed that higher PAH values were reported by Obini et al (2013), Ogoko (2014), and Ekanem et al (2019), while comparable values were reported by Muze et al (2020). The concentration of PAHs reported in the present study was lower than 1000 µg/kg recommended for soil cleanup by the Department of Petroleum resources, Nigeria (DPR 2002).…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…Reports have shown that indiscriminate spilling of petroleum products around automechanic workshops due to automobile repairs contributes to increased PAH levels in such environment (Farombi et al 2013;Obini et al 2013;Nwoko et al 2017). The mean PAH concentrations of the present study compared to related studies in Nigeria revealed that higher PAH values were reported by Obini et al (2013), Ogoko (2014), and Ekanem et al (2019), while comparable values were reported by Muze et al (2020). The concentration of PAHs reported in the present study was lower than 1000 µg/kg recommended for soil cleanup by the Department of Petroleum resources, Nigeria (DPR 2002).…”
Section: Discussionsupporting
confidence: 56%
“…Previous publications have reported the presence of PAHs in mechanic villages and automobile workshops (Ogoko 2014;Ekanem et al 2019;Muze et al 2020). The six USEPA target PAHs including phenanthrene, fluorene, benzo [α]anthracene, benzo [β]fluoranthene, and benzo[γ]fluoranthene, with concentrations ranging from 0.0184 ± 0.02 to 0.1385 ± 0.2 mg/kg were observed in Abakaliki automechanic village (Obini et al 2013).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Due to the high levels of PAH pollution occurring in the Niger Delta and their associated health risks, several studies have been conducted by collecting samples from different environments of the Niger Delta. Most of these environments include rivers, creeks, dumpsites, OEE sites, automobile repair shops, agricultural farms, and other urban areas (Abbas and Brack 2005;Ana et al 2009;Sojinu et al 2010;Nganje et al 2011;Olawoyin et al 2012;Oyo-Ita et al 2012;Adedosu et al 2012;Osuji et al 2012;Nduka et al 2013;Nganje et al 2014;Ogoko 2014;Asagbra et al 2015;Inam et al 2015;Nwineewii and Marcus 2015;Davies and Abolude 2016;Dosunmu et al 2016;Nwaichi et al 2016;Ekanem et al 2019;Ihuoma et al 2020).…”
Section: Fig 1 Herementioning
confidence: 99%